The Influence of Creative and Fun Learning Models through Project Based Learning (PjBL) Methods on Increasing Student Achievement - Anggraeni, Dini; Rahman; Hartati, Tatat; Iswara, Prana Dwija; Riswanto, Ari (International Conference on Elementary Education, 2022)
This study discusses the effect of using creative and fun learning models through the Project Based Learning (PjBL) method on increasing student achievement. The problem in this study is the low learning achievement of fifth grade students in Indonesian subject matter at the Integrated Islamic Elementary School (SDIT) Insani City of Sukabumi. The research method used is a quasi-experimental research design with Non-Equivalent Pre-test - Post-Test Control Group Design. Based on the normality, homogeneity, and t-test data from the pretest posttest data for understanding the concepts of students in the experimental class and the control class. The use of the Project Based Learning (PjBl) method for fifth grade students is expected to improve student achievement in Indonesian subjects at SDIT Insani Sukabumi City, West Java – Indonesia.